2020
DOI: 10.3847/1538-4357/abbb2e
|View full text |Cite
|
Sign up to set email alerts
|

A New Candidate Transitional Millisecond Pulsar in the Subluminous Disk State: 4FGL J0407.7–5702

Abstract: We report the discovery of a variable optical and X-ray source within the error ellipse of the previously unassociated Fermi Large Area Telescope γ-ray source 4FGL J0407.7–5702. A 22 ks observation from XMM-Newton/European Photon Imaging Camera (EPIC) shows an X-ray light curve with rapid variability and flaring. The X-ray spectrum is well fit by a hard power law with Γ = 1.7. Optical photometry taken over several epochs is dominated by aperiodic variations of moderate amplitude. Optical spectroscopy with Sout… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 71 publications
2
20
0
Order By: Relevance
“…This has led newly discovered low-mass X-ray binaries with positions compatible with Fermi -LAT GeV γ-ray sources to be consistently characterized as candidate tMSPs. The three sources in this category are 3FGL J1544.6-1125, which shows the X-ray moding unique to tMSPs (Bogdanov & Halpern 2015), 3FGL J0427.9-6704, for which the optical/X-ray and γray association is proven via periodic eclipses (Strader et al 2016;Kennedy et al 2020), and the recent discovery 4FGL J0407.7-5702 (Miller et al 2020). A fourth source, CXOU J110926.4-650224, is a suspected lowmass X-ray binary that shows optical and X-ray variability similar to the tMSPs including X-ray moding (Coti Zelati et al 2019).…”
mentioning
confidence: 94%
“…This has led newly discovered low-mass X-ray binaries with positions compatible with Fermi -LAT GeV γ-ray sources to be consistently characterized as candidate tMSPs. The three sources in this category are 3FGL J1544.6-1125, which shows the X-ray moding unique to tMSPs (Bogdanov & Halpern 2015), 3FGL J0427.9-6704, for which the optical/X-ray and γray association is proven via periodic eclipses (Strader et al 2016;Kennedy et al 2020), and the recent discovery 4FGL J0407.7-5702 (Miller et al 2020). A fourth source, CXOU J110926.4-650224, is a suspected lowmass X-ray binary that shows optical and X-ray variability similar to the tMSPs including X-ray moding (Coti Zelati et al 2019).…”
mentioning
confidence: 94%
“…Whether 4FGL J0935.3+0901 has this property can be checked with a targeted X-ray observation. The ratios of 0.5-10 keV X-ray fluxes to 0.1-100 GeV γ-ray ones for the tMSPs and candidates are ∼0.3-0.4, significantly higher than those of redbacks (e.g., Miller et al 2020), but the previously estimated flux ratio for 4FGL J0935.3+0901 (at 0.3-10 keV Xray band) was only ∼0.02. This inconsistency thus raises a question about the nature of 4FGL J0935.3+0901 and also about how to explain its double-peaked emission line feature.…”
Section: Introductionmentioning
confidence: 60%
“…These close MSP binaries contain a ≥ 0.1M ⊙ companion star, constituting a class sample that helps reveal not only the LMXB evolution processes (Chen et al 2013;Benvenuto et al 2014) but also intriguing physical properties of compact star binaries (Strader et al 2019 and references therein). Moreover, two of redbacks (PSR J1023+0038 and XSS J12270−4859; Archibald et al 2009;Bassa et al 2014) have been identified as transitional MSP (tMSP) systems and several as candidates (e.g., Miller et al 2020 and references therein):…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 0.1-100 GeV γ-ray luminosity is L γ = (1.35 ± 0.05) × 10 33 erg s −1 , giving an X-ray to γ-ray luminosity ratio of 0.003. This is lower than typical for redbacks (Miller et al 2020), with the only comparably low ratios observed for PSR J1622-0315 (Gentile 2018;Strader et al 2019) and the unusual source PSR J1816+4510 (Kaplan et al 2013), discussed in more detail below. Instead, the X-ray to γ-ray flux ratios and X-ray luminosities are more similar to black widows (e.g., Lee et al 2018), though nearly all black widows have shorter orbital periods than J1120.…”
Section: High-energy Propertiesmentioning
confidence: 66%